MOTIVASI BERWIRAUSAHA MELALUI PEMANFAATAN SAMPAH MENJADI PRODUK KREATIF DI SMA INSAN KAMIL BOGOR - Ria Susanti Johan; Desy Septariani; Widiyarini Widiyarini (Abdi Jurnal Publikasi, 2023)
Utilization of waste into creative products is one form of business that can generate economic and environmental benefits. This paper discusses the motivation for entrepreneurship through the use of waste into creative products at Insan Kamil High School, Bogor. Some of the things that have become the motivation for doing this business include growing environmental awareness among students, providing opportunities to develop creativity, and providing additional income alternatives. In implementing this business, it is necessary to carry out various activities such as collecting waste, sorting waste, and processing waste into creative products that have a sale value. In addition, it is also important to introduce creative products resulting from the utilization of waste to the public so that it can increase buying interest and maintain business continuity. Through the business of utilizing waste into creative products, students can learn to be entrepreneurs while protecting the surrounding environment.